2020
DOI: 10.1039/d0ra06920e
|View full text |Cite
|
Sign up to set email alerts
|

TiN nanotube supported Ni catalyst Ni@TiN-NTs: experimental evidence of structure–activity relations in catalytically hydrolyzing ammonia borane for hydrogen evolution

Abstract: Titanium nitride nanotubes (TiN-NTs) were fabricated using a hydrothermal – ammonia nitriding route, and non-noble metal nanosized Ni particles were anchored on the surface via a non-aqueous phase reduction–deposition strategy, to obtain the supported catalyst Ni@TiN-NTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…By contrast, our previous study has confirmed that the catalytic activity of Pt@Cu bimetal nanocrystals with same metal molar ratios present evidently inferior catalytic activity to Pt@Cu(9%)/TiO 2 , [28] which should be undoubtedly attributed to the positive effect of the carrier TiO 2 -NTs. [17] The turnover frequency (TOF) can be used to more precisely describe, and evaluate the catalytic performance of a given catalyst. [13] In view of the feature of the present catalytic hydrolysis reaction, we propose a concise but reasonable formula: TOF = [P × V H2 /R × T]/(n M × t), where V H2 denotes the H 2 volume produced from the hydrolysis reaction in given reaction time t; P and T separately represent the local atmospheric Figure 6.…”
Section: Catalysis Ability Of Pt@cu(x)/tio 2 On the Ab Hydrolysismentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, our previous study has confirmed that the catalytic activity of Pt@Cu bimetal nanocrystals with same metal molar ratios present evidently inferior catalytic activity to Pt@Cu(9%)/TiO 2 , [28] which should be undoubtedly attributed to the positive effect of the carrier TiO 2 -NTs. [17] The turnover frequency (TOF) can be used to more precisely describe, and evaluate the catalytic performance of a given catalyst. [13] In view of the feature of the present catalytic hydrolysis reaction, we propose a concise but reasonable formula: TOF = [P × V H2 /R × T]/(n M × t), where V H2 denotes the H 2 volume produced from the hydrolysis reaction in given reaction time t; P and T separately represent the local atmospheric Figure 6.…”
Section: Catalysis Ability Of Pt@cu(x)/tio 2 On the Ab Hydrolysismentioning
confidence: 99%
“…), [25,26] even certain nonnoble metals (e.g., Cu, Ni, etc. ), [17,27] to form more active sites on the interface/surface, effectively boosting the catalytic ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective synergy of phase constitution, inner texture, and surface topography of the multimetal catalysts is mostly responsible for the catalytic properties, which has been testified by many related studies. [24][25][26] In consideration of the pros and cons of different metals, compositing costly but high active Pt element with cheap but low active Cu element to fabricate efficient catalysts should be well worth the expectation and attempt.Based on our previous researches, [27,28] we hereby put forward an improved Galvani substitution protocol to effectively regulate the composition, size, and shape of the Pt|Cu nanocrystals via reasonably controlling additives (e.g., reductant, modifier, and A modified Galvani substitution protocol is proposed to fabricate serial Pt|Cu nanocrystals for hydrolyzing ammonia borane to generate H 2 gas. The as-fabricated Pt|Cu spheroidal nanocrystals with mean size of 75 nm hold porously hierarchical waxberry-shaped appearance, with more subtle Pt grain cladding on Cu nanospheres to build the nanocrystal cluster frameworks.…”
mentioning
confidence: 99%
“…Based on our previous researches, [27,28] we hereby put forward an improved Galvani substitution protocol to effectively regulate the composition, size, and shape of the Pt|Cu nanocrystals via reasonably controlling additives (e.g., reductant, modifier, and A modified Galvani substitution protocol is proposed to fabricate serial Pt|Cu nanocrystals for hydrolyzing ammonia borane to generate H 2 gas. The as-fabricated Pt|Cu spheroidal nanocrystals with mean size of 75 nm hold porously hierarchical waxberry-shaped appearance, with more subtle Pt grain cladding on Cu nanospheres to build the nanocrystal cluster frameworks.…”
mentioning
confidence: 99%